Evaluating efficacy and mechanism of traditional Chinese medicine in diabetes treatment: a meta-analysis and network pharmacology study - Tang, Shuai; Lin, Jie; Li, Gangyi; Guo, Huaijuan; Liu, Chang; Wu, Fuju (Frontiers in Endocrinology, 2025)
BackgroundDiabetes is a prevalent chronic metabolic disorder, and the rising rates of this condition, along with its complications, significantly threaten public health. Traditional treatments for diabetes have certain limitations in practical applications, and it is particularly important to find new, effective treatments with fewer side effects. With a long history and rich experience, traditional Chinese medicine (TCM) effectively treats diabetes.MethodsData from randomized controlled trials concerning TCM and its effects on diabetes were gathered and analyzed from various databases. A meta-analysis was conducted on the 58 selected articles, and the potential mechanisms of action of the active ingredients in TCM were examined using network pharmacology techniques.ResultsMeta-analysis of 58 randomized trials (n=7,318) demonstrated significant improvements in fasting glucose (MD=-0.53 mmol/L [-0.67,-0.39], P<0.00001), HbA1c (MD=-0.40% [-0.61,-0.20], P = 0.0001), and insulin resistance (HOMA-IR: MD=-0.90 [-1.51,-0.29], P = 0.004), alongside favorable lipid modulation (LDL: MD=-0.14 mmol/L, P = 0.0002). Network pharmacology revealed six core herbs (Astragalus membranaceus, Coptis chinensis, etc.) targeting 32 hub genes (AKT1, IL1B, PPARG, etc.) through three key pathways: insulin signaling (PI3K-AKT), inflammatory regulation (TNF/IL-17), and oxidative stress response (HIF-1/NRF2 axis). The polypharmacological effects were mediated by multi-component interactions involving quercetin, kaempferol, and stigmasterol.ConclusionTCM has demonstrated considerable effectiveness in managing diabetes. Through meta-analysis and network pharmacology research, this translational study establishes Level 1a evidence for TCM’s antidiabetic efficacy while decoding its systems-level mechanisms. The integrated methodology provides a paradigm for evaluating complex herbal interventions in metabolic disorders.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42024572433.